Immune response and cytokine production following immunization with experimental herpes simplex virus 1 (HSV-1) vaccines - Ďurmanová, Vladimíra; Sapák, Michal; Košovský, Ján; Režuchová, I; Kúdelová, Marcela; Buc, Milan; Rajčáni, Július (Folia microbiologica, 2008)
Balb/c mice were immunized with the recombinant fusion protein gD1/313 (FpgD1/313 representing the ectodomain of HSV-1 gD), with the non-pathogenic ANGpath gE-del virus, with the plasmid pcDNA3.1-gD expressing full-length gD1 and with the recombinant immediate early (IE) HSV-1 protein ICP27. Specific antibodies against these antigens (as detected by ELISA) reached high titers with the exception of the DNA vaccine. High-grade protection against challenge with the virulent strain SC16 was found following immunization with the pcDNA3.1-gD plasmid and with the gE-del virus. Medium grade, but satisfactory protection developed after immunization with the FpgD1/313 and minimum grade protection was seen upon immunization with the IE/ICP27 polypeptide. A considerable response of peripheral blood cells (PBL) and splenocytes in the lymphocyte transformation test (LTT) was found in mice immunized with FpgD1/313, with the pcDNA3.1-gD plasmid and with the live ANGpathgE-del virus. For lymphocyte stimulation in vitro, the FpgD1/313 antigen was less effective than the purified gD1/313 polypeptide (cleaved off from the fusion protein); both proteins elicited higher proliferation at the 5 mug per 0.1 mL dose than at the 1 mug per 0.1 mL dose. The secretion of Th type 1 (TNF, IFN-gamma and IL-2) and Th type 2 (IL-4 and IL-6) cytokines was tested in the medium fluid of purified PBL and splenocyte cultures; their absolute values were expressed in relative indexes. The PBL from FpgD1/313 immunized mice showed increased secretion of both T(H)1 (TNF) as well as T(H)2 (IL-4) cytokines (7-10-fold, respectively). Splenocytes from FpgD1/313 immunized mice showed a significant (23-fold) increase in IL-4 production.
Keywords: imunizace; Cell Line; protilátky virové; virové proteiny; cytokiny; Lymphocyte Activation; myši inbrední BALB C; Herpesvirus 1, Human; krevní buňky; aktivace lymfocytů; T-lymfocyty; Mice, Inbred BALB C; Viral Proteins; Blood Cells; kultivované buňky; Animals; lidé; vakcína proti viru herpes simplex; Herpes Simplex Virus Vaccines; Humans; zvířata; lidský herpesvirus 1; myši; buněčné linie; Simplexvirus; Antibodies, Viral; Cells, Cultured; Cytokines; T-Lymphocytes; Mice; Immunization